Collaboration between Sami and non-Sami formal and family caregivers in rural municipalities - Larsen, Lill Sverresdatter; Normann, Hans Ketil; Hamran, Torunn (Ethnic and Racial Studies, 2015)
Published version available at http://dx.doi.org/10.1080/01419870.2015.1080382 The aim of this study was to explore how caregivers experience collaboration in rural municipalities in northern Norway. We conducted fieldwork with a dementia team in addition to seventeen qualitative in-depth interviews with formal and family caregivers. The caregivers had ethnic Sami and ethnic Norwegian affiliation. The theme ‘negotiating ethnic and ethno-political positions’ was identified through thematic analysis and developed using positioning theory. Ethnicity involves dynamic and situated personal affiliations, and participants negotiate each other’s ethnic positions in practice. Negotiations of ethnic positions hamper collaboration between formal and family caregivers, and ethno-political positions reinforce stereotyped ethnic positions. This study contributes to the understanding of and the debate over positions on ethnocultural collaboration in health care. In practice, participants negotiate the health policy concept of ‘cultural facilitation’, which must be broadened to ensure equal health-care services.